Population studies and carrageenan properties of Chondracanthus teedei var. lusitanicus (Gigartinaceae, Rhodophyta) - Pereira, Leonel (2004)
Features of an intertidal population of Chondracanthus teedei var. lusitanicus, which occurs in sandy basins on rocky shores of part of the Portuguese coast (Buarcos, Figueira da Foz), were studied over one year. Biomass and plant size showed a small increase in early spring (April), a marked increase in early summer (June/July) and were at a minimum in late summer. There was generally more tetrasporophytes (4–32.5%) than female gametophytes (3–29%), which contrasts with other geographical regions where C. teedei populations have been studied, such as Brazil and France. However, non-fructified thalli predominated throughout the year. Phycocolloid extracts were compared for the various stages using spectroscopic methods (FTIR, FT-Raman, 1H- and 13C-NMR). These showed a hybrid carrageenan belonging to the lambda family in the tetrasporophyte and a hybrid kappa-iota-mu-nu carrageenan in the female gametophyte and non-fructified thalli. The average phycocolloid content was 34.9% dry weight, with a maximum of 43.6% in July. The combination of high available biomass and phycocolloid content makes this species a potentially important source of kappa/iota hybrid carrageenan in Portugal additional to the traditionally harvested carrageenophytes.